Changes of demand for occupation in Malaysian labour market - Abdul Hamid, Kamarul Hidayah (2012)
The issue of changes in the demand for occupation came to the forefront and generate much analyses, when rapid industrialisation and globalisation. Malaysian economy has been transformed from agriculture to services economy have resulted in the modification of structural demand for occupations in all sectors. The imbalanced in occupation structure in Malaysia was lead to tighten labour market in 1990s and these issues still unquestionable for policy makers and researchers. This study employed a set of data comprises micro level data from the Household Income Survey (HIS) for several years 2002, 2004 and 2007. This study has classified occupation into four groups namely; fourth, third, second and first skilled level workers. The classification for occupation groups are followed by Malaysia Standard Classification Occupation codes 2008 (MASCO 2008). The study focuses on professional and technical workers. This study sets out to examine the changes in the composition of occupational that take place and explore the reasons behind these changes for fifteen major sector and details on education sector in the case of Malaysia by using the decomposition approach. The changes in occupation demand are lead by two main factors whether technological change or trade. This study used the terms of within effects that represent the changes in technological change and between effects represent the changes in trade. In the component of within and between affects this study broken down into wage component and employment component to explain the changes in relative demand. These two hypotheses have been well tested using the Heckscher-Ohlin and Samuelson (HOS) models. First stage analysis for 15 major industries group shows that professional group had a decreasing trend during the period 2002 to 2007. The main causes of the decreasing are mainly due to changes in wage structure. The changes in wage structure are dominated by technological change or we called in this study as within effects. On the other hand, technical workers had increasing in relative demand during the sample period of study and the main factor that was lead to these changes is employment structure. At the second stage of analyses, this study focuses on education sector. The education sectors are divided into three sub sector known as primary education, secondary education, and tertiary education sector. Overall, the results show that in all sub sectors, employment structure dominated the changes in relative demand for labour in education sector. Looking at the changes in professional workers, this group shows an increasing trend in relative demand at tertiary education sub sector during the sample period of study. On the contrary, technical workers recorded a decreasing trend in relative demand especially in primary education sub sector.